FORMULA ACTION LEARNING AS A STRATEGY TO DEAL WITH THE PROBLEM OF ART EDUCATION IN FORMAL SCHOOLS - Rachmat Rachmat (Universitas Negeri Makassar, 2021)
Art education is an activity to make humans able to survive and be able to show their identity in the future. The purpose of writing this article is to describe the current problems of education, and efforts to deal with the current problems of art education. The method used is a phenomenological approach, and data collection is done by conducting observations and interviews. The results showed that some of the learning problems were the lack of facilities and infrastructure, the competence of art teachers in schools, and the lack of student interest in learning. One effort to overcome this is through action learning models in learning to form students' inductive thinking skills.